Mechanical circulatory support for cardiovascular complications in a young COVID‐19 patient - Popov, Aron Frederik (J Card Surg, 2020)
Background: The current coronavirus (COVID‐19) pandemic is associated with severe pulmonary and cardiovascular complications. Case presentation: This report describes a young patient with COVID‐19 without any comorbidity presenting with severe cardiovascular complications, manifesting with pulmonary embolism, embolic stroke, and right heart failure. Conclusion: Management with short‐term mechanical circulatory support, including different cannulation strategies, resulted in a successful outcome despite his critical cardiovascular status.